Efficiency of Motivation Development Models for Hygienic Skills - Tscymbalystov, Alexander V.; Kopytov, Alexander A.; Saraykina, Olga S.; Gontarev, Sergey N. (Journal of History Culture and Art Research, 2017)
The combined influence of a family and a state plays an important role in the development of an individual. This study is aimed at the model effectiveness evaluation concerning the development of oral hygiene skills among children living in families (n = 218) and being under the care of a state (n = 229). The groups were created among the children who took part in the study: the preschoolers of 5-7 years, schoolchildren of 8-11 years and adolescents of 12-15 years. During the initial examination, the hygienic status of the oral cavity before and after tooth brushing was evaluated. After that, subgroups were formed in each age group according to three models of hygienic skills training: 1) computer presentation lesson; 2) one of the students acted as a demonstrator of the skill; 3) an individual training by a hygienist. During the next 48 hours children did not take hygienic measures. Then the children were invited for a control session to demonstrate the acquired skills of oral care and evaluate the effectiveness of a model developing the skills of individual oral hygiene. During the control examination, the hygienic status was determined before and after the tooth cleaning, which allowed to determine the regimes of hygienic measure performance for children with different social status and the effectiveness of hygiene training models.